Study on the control effect of Empedobacte brevis on cherry fruit fly - Zhang, Wenhui; Duan, Jiayu (Pacific International Journal, 2024)
Abstract: Fruit fly is a major boring pest of cherry fruits during the color change and maturity period. It causes serious damage and affects the quality and economic benefits of cherry fruits. In order to clarify the control effect of Empedobacter brevis on cherry fruit fly and provide basis for guiding scientific medication use. The test adopts the conventional spray method, and uses 60g•L-1 spinetoram suspension as a control to compare and analyze the control effects of different dosages of Empedobacter brevis suspension on cherry fruit fly. The results show that on the three cherry varieties of Red lantern, Tieton and Napoleon, the control effects of Empedobacter brevis 600 times and 800 times and spinetoram 1000 times are better, and the control efficiency reaches more than 78-80%. There is no significant difference in control effects among the three, and they are safe for cherry trees. In cherry production, Empedobacter brevis can be promoted and applied as an effective biological agent to control fruit flies.